The importance of computer literacy in delivering better services: a case study in PUSAKA, Kuching Sarawak / Azwandy Mahli & Siti Hanisah Mateni - Mahli, Azwandy; Mateni, Siti Hanisah (Academia Industry Networks, 2007)
Malaysia changes from the traditional way to the using ICT in administration within the public sector can be traced back in the period 1980s. Nowadays, employees in the government sector should know how to use computer in their daily activities in doing job. In other word, there are important to the employees advance in computer to give the better services. The pervasiveness of computers is continuing to grow at an outstanding rate. Computers are also always changing; they are becoming smaller, faster and more powerful. To keep up with the changes a good knowledge of computer basics might come in handy. Computer literacy is just like any other acquired skill, it is easier to expand on what is already known than to try to start fresh with no prior knowledge or experience at all. Computer literacy is considered to be a very important skill to possess while in the first world. Employers want their workers to have basic computer skills because their company becomes ever more dependent on computers.